Imported Inflation and Interest Rate Turnaround: Challenges for the ECB - Überblick (Wirtschaftsdienst)
Abstract Inflation in Germany and the euro area as a whole has risen sharply in recent months. This development is mainly driven by rising energy prices. The ECB has announced that it will phase out the APP bond-buying programme in the third quarter and plans to raise the key interest rate this summer. Are the planned measures sufficient to lower inflation? It seems important to limit inflation expectations in order to prevent wage-price spirals. It also begs the question about how effective monetary policy is if primarily (imported) energy price inflation has to be fought. In addition, there must be a discussion about the contractionary effects of interest rate hikes on the economy as a whole, which is already fragile due to the coronavirus crisis and the Ukraine war.